ANALISIS FAKTOR- FAKTOR YANG MEMPENGARUHI GOOD CORPORATE GOVERNANCE RATING ( Studi Kasus pada Perusahaan yang Terdaftar Dalam Laporan Indeks CGPI Tahun 2009-2011) - Pamungkas, Ichsan; Muid, Dul (Diponegoro Journal of Accounting, 2013)
This research aims to examine the effects of firm’s characteristics on Good Corporate Governance (GCG) rating, refers to the study done by Ariff et al (2007) in Malaysia. There are differences between this research and the research done by Ariff et al, such as samples and regression tools used. This research analyzing firm characteristics as determinants of good corporate governance score in Indonesia. The firm’s characteristics are divided into 8 variables: profitability, ownership concentration, firm’s size, leverage, growth of sales, firm’s age, countries of operation, and firm’s valuation. The population of this research is all firms which are listed in Corporate Governance Perception Index (CGPI) in year 2009-2011. Sampling method used in this research is purposive sampling. Based on purposive sampling that has been done, the collected samples are 11 firms. Analysis technique used in this research is multiple linear regression because score based on criterias made by IICG is used to measure the dependent variables.The empirical results show that ownership concentration, firm size, firm’s age, and firm’s valuation have positively significant influenced on assesment of GCG mechanism. High percentage of ownership, increasing ages, Tobins’s Q ratio and high total asset will affect higher CG score. While profitability, leverage, growth of sales, and countries of nation has no significant influenced on GCG rating.